Entre le poids des traditions et les appels de la modernité : la gouvernance du Musée national des beaux-arts du Québec (1933-1963) - Porter, John (Muséologies, 2021)
The Musée national des beaux-arts du Québec is the oldest of our state museums. It had been in the making since 1922 and opened its doors in 1933, in the middle of an economic crisis. It was also in a difficult context that its identity, collections and outreach initiatives gradually took shape under the aegis of directors whose backgrounds were as different as they were complementary. Among them, the visionary and resilient Paul Rainville (1887-1952) stands out. An inspiring personality, he was the model for transparent management, accountability and concern for serving the community well. He left a varied and lasting imprint on a national institution which, until 1963, was known as the “Musée de la Province de Québec.” If Rainville had lived in our time, he would no doubt have known how to cope with our governance regulations and find innovative ways to overcome the obstacles confronting our museal institutions both large and small.